BALANCED SCORECARD IN ENVIRONMENTAL SCIENCES: A TOOL FOR SUSTAINABLE MANAGEMENT - Picanço, Marcio Luiz Repolho; Guimarães, Jarsen Luis Castro; Camargo Júnior, Raimundo Nonato Colares; da Silva, Mauro Marinho; da Silva, Welligton Conceição; da Cruz, Simone Lobato Ferreira (ARACÊ, 2025)
This article proposes the implementation of the Balanced Scorecard (BSC) as a management tool adapted to environmental sciences, focusing on integrating economic and ecological objectives. The research explores how the BSC can be employed to promote sustainable management that addresses natural resource conservation and climate change mitigation. Using secondary data and a descriptive approach, the study examines the feasibility of incorporating a new sustainability perspective into the traditional BSC model. The article highlights that by adding environmental and social indicators, the BSC can become a more comprehensive and effective strategic tool, capable of responding to regulatory pressures and stakeholder expectations. However, the absence of quantitative analyses and empirical testing underscores a gap in validating the proposed model, indicating the need for future studies to consolidate this integration.